EFEKTIVITAS PENERAPAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SDN 21 TANGNGA-TANGNGA - Wijayanto, Syifa Nursabrina; Patta, Rahmawati; Pagarra, Hamzah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study examines the implementation of differentiated learning at SDN 21 Tangnga-Tangnga. The purpose of this research is to apply general knowledge about differentiated learning in science subjects, to identify significant differences in learning outcomes between the experimental and control classes, and to evaluate the effectiveness of differentiated learning in improving course performance. This study employs a quasi-experimental control group design with a pretest-posttest methodology. The research population consists of 29 fifth-grade students from SDN 21 Tangnga-Tangnga. Using the Non-Probability Sampling approach, a sample of 15 individuals from class V A was selected. Data collection methods include tests, surveys, documentation, and observations. The data analysis techniques used are homogeneity tests, normality tests, and hypothesis testing, combined with descriptive and inferential statistical analysis using IBM SPSS Version 23. The conclusions of this study indicate that students greatly benefit from varied teaching methods. Inferential statistical analysis shows that the learning outcomes of the experimental class students have a probability value of less than 0.05, specifically a probability value of 0.003, which is smaller than the α level (0.003 < 0.05), leading to the rejection of  and acceptance of . Thus, it can be concluded that, in terms of learning outcomes, the fifth-grade students at SDN 21 Tangnga-Tangnga, Bantaeng Regency, have benefited from the implementation of differentiated learning.